Kritik terhadap Individualisme Metodologis dalam Ilmu Ekonomi - Sandi, Herdito (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2013)
The advancement of mainstream economics, especially in neoclassical-Austrian school, can be traced back to the implementation of methodological individualism, a methodological doctrine stating that every explanation on the macro level (i.e. society, economy, and politics) is based on the foundation of explanation on the micro level (individual) as an ontological unit. This is a kind of ‘atomism’ that could be found clearly in Hobbes, JS. Mill, and the Austrian School. This methodology produces curva and modelling in economics. We might need to distinguish tightly between political individualism and methodological individualism. Political individualism starts from the general assumption that freedom contributes to the individual development and the prosperity of the society and brings forward some practical propositions to support it. Meanwhile, methodological individualism does not bring particular proposition and condition, but simply points to the means based on the process of economy in the action of the individual. This paper tries to construct a critical view concerning the methodological individualism in order to open the possibility for other methodologies in economics.